Proper surgical extent for clinical Stage I right colon cancer - Han Deok Kwak; Jun Seong Chung; Jae Kyun Ju; Soo Young Lee; Chang Hyun Kim; Hyeong Rok Kim (Journal of Minimal Access Surgery, 2022)
Purpose: Pre-operative evaluation identifying clinical-stage affects the decision regarding the extent of surgical resection in right colon cancer. This study was designed to predict a proper surgical resection through the prognosis of clinical Stage I right colon cancer. Patients and Methods: We included patients who were diagnosed with clinical and pathological Stage I right-sided colon cancer, including appendiceal, caecal, ascending, hepatic flexure and proximal transverse colon cancer, between August 2010 and December 2016 in two tertiary teaching hospitals. Patients who underwent open surgeries were excluded because laparoscopic surgery is the initial approach for colorectal cancer in our institutions. Results: Eighty patients with clinical Stage I and 104 patients with pathological Stage I were included in the study. The biopsy reports showed that the tumour size was larger in the clinical Stage I group than in the pathological Stage I group (3.4 vs. 2.3 cm, P < 0.001). Further, the clinical Stage I group had some pathological Stage III cases (positive lymph nodes, P = 0.023). The clinical Stage I group had a higher rate of distant metastases (P = 0.046) and a lower rate of overall (P = 0.031) and cancer-specific survival (P = 0.021) than the pathological Stage I group. Compared to pathological Stage II included in the period, some of the survival curves were located below the pathological Stage II, but there was no statistical difference. Conclusion: The study results show that even clinical Stage I cases, radical resection should be considered in accordance with T3 and T4 tumours.